Pendidikan Kecakapan Hidup Melalui Pelatihan Pembuatan Kain Tenun di Pondok Pesantren Miftahul Huda Pabelan Kabupaten Semarang - Ma'as Shobirin (LP2M of Institute for Research and Community Services - UIN Walisongo, 2017)
In the modern era, there are still many young people who dropped out of school, including at boarding school. Economic factor that make them could not be a formal education. Nevertheless, schools remains committed to make a breakthrough in order to provide life skills for students who drop out of school. Life skill education program through the manufacture of woven fabrics organized in boarding school Miftahul Huda Pabelan Kab. Semarang is expected to provide knowledge as well as to equip the students to have the skills to live. This activity involves several parties such as Home Industry